2003
DOI: 10.1034/j.1600-0560.2003.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Bednár tumor associated with dermal melanocytosis: melanocytic colonization or neuroectodermal multidirectional differentiation?

Abstract: Reported herein is a singular case of Bednár tumor associated with dermal melanocytosis. Although the coexistence of these processes implicates colonization of the DFSP by constituent dermal melanocytes, the mixed immunophenotype (CD34+ or Mart-1+ cells) of dispersed dermal spindle cells hints at the possibility of a common cell of origin: the putative neuromesenchymal cell. In effect, the Bednár tumor could represent one part of a spectrum of neural crest-derived dermal tumors that includes dermal melanocytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…30,34 More recent report indicated that dermatofibrosarcoma protuberans is probably a neuromesenchymal neoplasm based on the observations in Bednar tumors. 31 In our study, D2-40 was positive in all dermatofibromas, including cellular fibrous histiocytoma. In contrast, none of the dermatofibrosarcoma protuberans was labeled, although four cases showed a patchy and faint background staining.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…30,34 More recent report indicated that dermatofibrosarcoma protuberans is probably a neuromesenchymal neoplasm based on the observations in Bednar tumors. 31 In our study, D2-40 was positive in all dermatofibromas, including cellular fibrous histiocytoma. In contrast, none of the dermatofibrosarcoma protuberans was labeled, although four cases showed a patchy and faint background staining.…”
Section: Resultsmentioning
confidence: 79%
“…[22][23][24][25][26][27] Schacht et al 27 also demonstrated the expression of D2-40 in some other nonendothelial cells beyond the above-mentioned cells To date, there are controversies and uncertainties regarding the histiogenesis of dermatofibromas and dermatofibrosarcoma protuberans. [28][29][30][31] For dermatofibroma, various cells of origin, including fibroblast, histiocyte, and endothelial cell, have been hypothesized. Some authors suggested myofibroblastic derivative for cellular fibrous histiocytoma given its reactivity for a1-smooth muscle actin.…”
Section: Resultsmentioning
confidence: 99%
“…197 The Bednar tumor has also been shown to express a mixed immunophenotype (CD34-or Mart-1-positive) in dispersed dermal spindle cells within a DFSP-like lesion suggesting a common cell of origin, namely, a putative neuromesenchymal cell, the potential cell of origin of all neural crest-derived dermal tumors including DFSP. 198 This overlap of histologic and immunohistochemical phenotypes may indicate the existence of a spectrum of neuromesenchymal conditions that range from purely melanocytic lesions (dermal melanocytosis and blue nevi), to varied proportions of melanocytic and neuromesenchymal elements (cellular blue nevi, desmoplastic melanomas, and Bednar tumors), to purely mesenchymal lesions (DFSP).…”
Section: Cd34 Expression In Malignant Melanomamentioning
confidence: 99%
“…. It is seen in young to middle-aged adults in the fourth decade with very occasional cases in the pediatric age group [6,7] . The most common site of the bednar tumor is trunk and proximal extremities [8,9,10] .…”
Section: Discussionmentioning
confidence: 99%